Rest Area Development as an MSME Center in Kenongo Village, Malang Regency - Putri, Diestya Galuh Eka; Salsabila, Julia; Choirani, Qurotul Aini Dwi Ratna; Mutiara, Elok (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2025)
The growth of MSMEs can create job opportunities, build infrastructure and increase community income at the village level. For example, Kenongo Village in Jabung District, Malang Regency has become an MSME-based village. The Kenongo Village Government is currently planning the design of a Central Area which includes a Rest Area and MSME Shopping Center. This central area aims to optimize MSME activities through several design approaches which will answer existing problems. In preparing the Rest Area design concept, several stages were carried out. The first stage is an analysis of the needs and potential of the area. The second stage is concept design. The third stage is detailed design. The final stage is evaluation and improvement, which includes design evaluation and improvement based on input from the village and community. The method used in this design is participatory design, which is an approach to the design process that involves users. The goal is to create products and services that better suit users' needs and expectations by leveraging people's knowledge and experience. Design solutions in this design Design solutions in this design include master plan design solutions for the Kenongo Village shopping tourism center and the Kenongo Village Rest Area.